Mammalian phospholipase D: activation by ammonium sulfate and nucleotides. - Nakamura, S (1995)
Phospholipase D (PLD) associated with the rat kidney membrane was activated by guanine 5'-[gamma-thio]triphosphate and a cytosol fraction that contained ADP-ribosylation factor. When assayed by measuring the phosphatidyl transfer reaction to ethanol with exogenously added radioactive phosphatidylcholine as substrate, the PLD required a high concentration (1.6 M) of ammonium sulfate to exhibit high enzymatic activity. Other salts examined were far less effective or practically inactive, and this dramatic action of ammonium sulfate is not simply due to such high ionic strength. Addition of ATP but not of nonhydrolyzable ATP analogue adenosine 5'-[beta, gamma-imido]diphosphate further enhanced the PLD activation approximately equal to 2- to 3-fold. This enhancement by ATP needed cytosol, implying a role of protein phosphorylation. A survey of PLD activity in rat tissues revealed that, unlike in previous observations reported thus far, PLD was most abundant in membrane fractions of kidney, spleen, and liver in this order, and the enzymatic activity in brain and lung was low.